2017
DOI: 10.4103/ija.ija_501_16
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of Video Stylet and flexible fibre-optic bronchoscope in the performance of intubation in adult patients

Abstract: Background and Aims:Video Stylet (VS) is a new intubating modality that provides real-time video of endotracheal intubation (ETI). This device does not need alignment of the oral, pharyngeal and tracheal axes to view glottis and can be used in patients with limited mouth opening. The aim of this study was to compare flexible fibre-optic (FO) bronchoscope with VS in elective surgical patients in apparently normal airway patients requiring oral ETI.Methods:Sixty patients undergoing elective surgery under general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Another study was performed involving 60 patients undergoing elective procedures in the supine position with the normal airway to compare the time required for intubation between the VS and the FO bronchoscope, showing an 18.5 s difference between the groups with a greater delay when using the FO bronchoscope. Moreover, no statistically significant differences were found in hemodynamic response or complications [ 10 ]. A study conducted by Ong et al [ 16 ] was performed to compare the VS and the Macintosh laryngoscope under 4 different conditions, which were normal airway, immobilization of the cervical spine, tongue swelling with cervical spine fixation, and tongue edema.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study was performed involving 60 patients undergoing elective procedures in the supine position with the normal airway to compare the time required for intubation between the VS and the FO bronchoscope, showing an 18.5 s difference between the groups with a greater delay when using the FO bronchoscope. Moreover, no statistically significant differences were found in hemodynamic response or complications [ 10 ]. A study conducted by Ong et al [ 16 ] was performed to compare the VS and the Macintosh laryngoscope under 4 different conditions, which were normal airway, immobilization of the cervical spine, tongue swelling with cervical spine fixation, and tongue edema.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size was calculated by comparing the intubation time between using the VS and FO maneuver in the lateral position of open abdominal surgery cases, as previously reported [ 10 ]. The mean time of intubation was approximately 19.7 ± 2.8 s in the VS group and approximately 38.2 ± 6.9 s in the FO maneuver group (Standard deviation was calculated from the given 95% CI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike VS, however, FOB with MA significantly reduced the time to see the glottis and time to complete intubation, as well as the cumulative success rate. In a previous study where a skilled anesthesiologist performed an intubation using FOB in preoperative patients with normal airways, the median time to complete intubation was measured as 38.2 seconds [ 15 ]. In this study, considering that the median time to complete intubation was 46 seconds when using FOB alone and 31 seconds when using FOB with MA, it may be expected that a novice operator could intubate at the level of a skilled anesthesiologist with the assistance of MA.…”
Section: Discussionmentioning
confidence: 99%
“…A previous clinical study comparing the performance of VS and FOB alone revealed that FOB had a better success rate of intubation (VS vs. FOB and 73.3% vs. 90%), but the use of VS enabled faster completion of intubation (VS, 19.7 (19–21) seconds vs. FOB 38.2 (36–41) seconds) [ 15 ]. In contrast, in this study, compared with FOB alone, VS alone was superior with respect to the success rate of intubation and time to complete intubation.…”
Section: Discussionmentioning
confidence: 99%